Estado poblacional de Echinometra lucunter (Echinoida: Echinometridae) y su fauna acompañante en el litoral rocoso del Caribe Colombiano - Monroy López, Mario (2005)
Population state of Echinometra lucunter (Echinoida: Echinometridae) and its accompanying fauna on Caribbean rocky littoral from Colombia. In order to know the current condition of the Echinometra lucunter population in the Colombian Caribbean, ten zones of the most representative rocky-shore were selected for sampling between November 2002 and May 2003. In each zone, four transects of 10.25 m2 were located parallel to the coast, and measured with a 0.25 m2 quadrant under the tide level. Two subsamples of 0.01 m2 were chosen from each quadrant, in order to determine the sea urchin heights and its associated fauna. This species was found in nine of the selected zones where the rocky-shore was of sedimentary origin and was absent in Punta Gloria because of the igneous origin of the rock, that the sea urchins cannot bore. The greatest average densities were obtained in Zapsurro and Inca Inca with 69 and 65 ind/m2 respectively; these are high values for the Caribbean Sea, whereas Acandí and Punta Betín had the lowest because of continental water discharges. The most frequent test diameter was between 25 and 40 mm (smaller on the western zones). The density of E. lucunter and of its associated fauna (including the endemic Ophiothrix synoecina) in the Santa Marta area decreased in the last decade. Rev. Biol. Trop. 53(Suppl. 3): 291-297. Epub 2006 Jan 30.